Local intracerebral form of diffuse leptomeningeal glioneuronal tumor – a new entity of the group of epileptogenic neoplasms? - V. S. Khalilov; A. N. Kislyakov; A. A. Kholin; U. A. Kukota; N. A. Medvedeva; A. S. Shapovalov; A. E. Druy (Русский журнал детской неврологии)
Diffuse leptomeningeal glioneuronal tumor was introduced into the World Health Organization classification of central nervous system tumors in 2016. According to the actual World Health Organization classification of central nervous system tumors emerged in 2021, its reliable verification requires the combination of specific pathomorphological and molecular-genetic features as well as data of the neuroimaging. Typically occurring in children and adolescents these tumors are characterized by widespread diffuse leptomeningeal dissemination along the neuraxis and demonstrate a tendency to abundant contrast enhancement resulting in a specific magnetic resonance imaging appearance. Despite this, and the rather rare incidence, a number of publications have reported an increasing number of atypical cases of diffuse leptomeningeal glioneuronal tumor suggesting that the spectrum of clinical manifestations, molecular-genetic and radiological criteria of this tumor is not fully disclosed and requiring further comprehensive investigations. The article presents the experience of complex, interdisciplinary diagnosis of diffuse leptomeningeal glioneuronal tumor with atypical radiological picture in a child with focal structural epilepsy.